Polycystic Ovary Syndrome Functional Investigation and Clinical Application - Wang, Zhengchao (IntechOpen, 2022)
Polycystic ovary syndrome (PCOS) is a heterogeneous hormone-imbalance disorder that occurs in reproductive-aged women worldwide and is characterized by hyperandrogenism, ovulatory process dysfunction and polycystic ovaries. This book includes two sections that cover the pathogenesis and treatment of PCOS. It provides a comprehensive overview of the latest PCOS research to benefit the population of women with this disorder.